Control of crystal size tailors the electrochemical performance of α-V2O5 as a Mg2+ intercalation host. Issue 22 (30th May 2021) - Johnson, Ian D.; Stapleton, Natalie; Nolis, Gene; Bauer, Dustin; Parajuli, Prakash; Yoo, Hyun Deog; Yin, Liang; Ingram, Brian J.; Klie, Robert F.; Lapidus, Saul; Darr, Jawwad A.; Cabana, Jordi
Abstract : Nanosizing α-V2 O5 inhibits delamination during cycling in Mg electrolytes, reducing the voltage hysteresis and energy loss on the first cycle. This observation indicates that other factors, not just Mg diffusion, contribute to this energy loss. Abstract : α-V2 O5 has been extensively explored as a Mg 2+ intercalation host with potential as a battery cathode, offering high theoretical capacities and potentials vs. Mg 2+ /Mg. However, large voltage hysteresis is observed with Mg insertion and extraction, introducing significant and unacceptable round-trip energy losses with cycling. Conventional interpretations suggest that bulk ion transport of Mg 2+ within the cathode particles is the major source of this hysteresis. Herein, we demonstrate that nanosizing α-V2 O5 gives a measurable reduction to voltage hysteresis on the first cycle that substantially raises energy efficiency, indicating that mechanical formatting of the α-V2 O5 particles contributes to hysteresis. However, no measurable improvement in hysteresis is found in the nanosized α-V2 O5 in latter cycles despite the much shorter diffusion lengths, suggesting that other factors aside from Mg transport, such as Mg transfer between the electrolyte and electrode, contribute to this hysteresis. This observation is in sharp contrast to the conventional interpretation of Mg electrochemistry. Therefore, this study uncovers critical fundamental underpinning limiting factors in Mg battery electrochemistry, and constitutes a pivotal step towards a high-voltage, high-capacity electrode material suitable for Mg batteries with high energy density.